Wringinputih: Destinasi Desa Wisata yang Memanjakan Sejuta Rasa bagi Wisatawan Lokal dan Mancanegara - Purwowibowo Purwowibowo; Budhy Santoso; Kris Hendrijanto; Syech Hariyono; Djoko Wahyudi; Belgis Hayyinatun Nufus (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract This article focuses on mangrove ecotourism in Wringinputih Village, Muncar District, Banyuwangi Regency.Wringinputih Village, is a new ecotourism destination that is very attractive to both local and foreign tourists.This is related to the success of mangrove forest conservation carried out by coastal communities through community empowerment and their active participation.Through a bottom - up model and managed based on local wisdom by involving as many coastal communities as possible, finally various touirsm objects based on mangrove forests in Wringinputih Village can be realized and become a potential and attractive alternative tourist destination that is visited by many tourists.With qualitative methods and in-depth interviews with tourist managers, community leaders, and tourists in the village, there is enough data to explain this tourist village destination.As a result, Wringinputih village has become some attractions for potential ecotourism based on mangrove forests and others objects developed by local communities and has brought in local and foreign tourists so that it’s can accelerate activities and open employment opportunities for the community and increase their income. Keywords: Wringinputih, Ecotourism, Mangrove Forest, Tourism Destination